Improving Sociology Learning Outcomes through theType Cooperative Learning Model STAD (Student Teams Achievement Division) at SMA Negeri 3 South Buru - Imanuela A. Solissa; R. Tutupary; Lambertus J. Lokollo (Peneliti.net, 2021)
The purpose of this study was to determine the STAD (type of cooperative learning modelStudent Teams Achievement Division) in improving sociology learning outcomes in grade X IPS 2 students at SMA Negeri 3 Buru Selatan. This research is classified as ClassroomAction Research. This study refers to the Spiral Model of Kemmis and Taggrat. The results showed that thetype of cooperative learning model STAD can improve learning outcomes of sociology of social interaction material concepts in class X-iis2 SMA Negeri 3 Buru Selatan. From these results it can be concluded that in the first cycle the students have not reached the criteria of completeness and in the second cycle they have achieved the KKM results very well. And thus do not continue in the next cycle